Deviation or Glocalization? Rhetorical Differences in Research Article Introductions Written by International, English FL, and Indonesian L1 Authors - Arianto, M. Affandi; Haq, Maulluddul; Jufrizal, Jufrizal; Saputra, Dwi Bayu; Syafrina, Dewi (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Following English rhetorical conventions in English academic texts, especially by non-native English authors, does not necessarily mean disregarding some rhetorical practices of their national language. Although investigating English RAs has largely been focused on how the textual structure of the section is written in English by native English speakers and non-native English speakers, there has a limited empirical attention so far related to the investigation of rhetorical differences between RA introductions written in English and those written in Indonesian. After a thorough genre-based investigation of 60 RAs published from 2019 to 2023 using the modified CARS model (Swales, 1990, 2004), this study has revealed that the use of each rhetorical style, including moves, steps, and patterns, in English and Indonesian RA introductions is different. The result indicates that although the moves and steps display a close affinity with the CARS model, we found higher use of Move 1, i.e., establishing a territory, in the language teaching RA introductions written in Indonesian than in English. On top of that, while international authors (IAs) established their niches adequately, Indonesian authors (Eng-FL) established their niches inadequately, seemingly due to the influence of their national language (Indonesian). Moreover, the Indonesian language not only affects the frequency of occurrence of the moves and steps but also contributes to the pattern deviations found in the English RA introductions written by the Indonesian authors. This study provides pedagogical implications for academic writing and insights for Indonesian authors to write English articles using English rhetorical styles.